Research Study Design for Teaching and Testing Fire Safety Skills with AR and VR Games - Kimmo Tarkkanen; Anttoni Lehto; David Oliva; Brita Somerkoski; Timo Haavisto; Mika Luimula (United States, 2022)
Virtual and augmented reality (VR & AR) games can provide innovative methods for teaching and learning important skills relating to fire safety. However, in an emergency context, testing the acquired knowledge and skills, i.e. verifying the learning, can be challenging. In this paper, we ask how the interplay between AR and VR could support learning verification. We describe two standalone games of both types, which interchangeably teach fire safety skills to children and verify their learning results. In particular, we describe the planned learning paths and research study designs for verification studies within and between these games to answer the above question. By operationalizing the two cases, the paper ends in proposing more generalized study design for AR and VR research in a fire safety context.
11th IEEE International Conference on Cognitive Infocommunications, CogInfoCom 2020, Proceedings, September 23-25, 2020